Study of The Problems of Minor Irrigation PEO Publication No 40 - Planning Commission (Planning Commission, 1961)
The Council approved the objectives of removal of unemployment, reduction in poverty and inequalities and continued progress towards self-reliance and generally welcomed the proposals in the Draft Plan in furtherance of these objectives. The Council approved the corresponding increased allocations for agriculture, rural development, irrigation, flood control and power and village and small-scale industries. The Council emphasized that these larger allocations alone would not benefit poorer sections of the people unless necessary institutional and administrative changes are made to ensure that benefits do indeed reach those for whom they are intended. Attention was especially drawn in this connection to the importance of speeding up the implementation of land reforms and of mobilising peasants organisations for this purpose.
Planning Commission Govt. of India